2017
DOI: 10.1016/j.jclepro.2017.01.107
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated sites in China: Countermeasures of provincial governments

Abstract: Contaminated sites have caused worldwide attention and been dealt with through a variety of policies and practices both nationally and regionally. Unlike the US, Canada, Japan, and Europe, which have accumulated rich experiences in contaminated site management, China, facing serious contaminated site issues, still lacks effective strategies on issues such as remediation standards, funding resources, accountability, and stakeholders coordination. This paper collected policies for contaminated site management fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 17 publications
0
15
0
2
Order By: Relevance
“…External stakeholders can provide incentives and disincentives through their dynamic allocation of resources. For example, the government may provide tax incentives, government subsidies and policy loans (Lee et al , ; Li et al , ). The polluter pays principle (PPP) also supports governments taxing polluters for their negative externalities.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…External stakeholders can provide incentives and disincentives through their dynamic allocation of resources. For example, the government may provide tax incentives, government subsidies and policy loans (Lee et al , ; Li et al , ). The polluter pays principle (PPP) also supports governments taxing polluters for their negative externalities.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Rodrigues et al (2009) reviewed and analysed several national contaminated land policy regimes that were already in place to assess common elements and to identify specific needs for developing of national soil policies. Li et al (2017) reported advanced legal strategies to prevent soil contamination in the US, the Netherlands and Great Britain. Swartjes et al (2012) reviewed the state of the art of contaminated site management in the Netherlands regarding policy framework and risk assessment tools.…”
Section: National Soil Contamination Instrumentsmentioning
confidence: 99%
“…Around the world, a wide range of industrial activities, waste disposal in uncontrolled landfills, mining, applications of agrochemicals, sewage sludge, and livestock waste, and environmental accidents, have left a legacy of contaminated sites (Mirsal, 2008;Li et al, 2017;Cachada et al, 2018;Gómez-Lavín et al, 2018;Gu et al, 2018;Romero-Baena et al, 2018). Contaminated soil can be found in agricultural land, forests, and urban and industrial areas (Li et al, 2018;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Contaminated sites (also referred to brownfield) are sites with pollution hazards beyond acceptable risk levels for human or ecosystem health (Lu et al 2015b;MEEPRC 2014). According to conservative estimates, over 200,000 contaminated sites were formed in China during the rapid urbanization and industrialization, and 320 of them were identified as seriously polluted with a coverage of more than 5 million hectares (Li et al 2017a). However, due to lack of relevant laws and regulations, some contaminated sites were directly redeveloped and utilized without effective risk assessment and remediation (Li et al 2018).…”
Section: Ecological Remediation Of Contaminated Sitesmentioning
confidence: 99%